THE NEW LINK BETWEEN ART FESTIVAL AND THE MEDIA: THE ENGAGEMENT OF A MEDIA INSTITUTION IN SURABAYA ART FESTIVAL - Rachmah Ida (Humaniora, 2014)
This paper is an attempt to investigate a new trend of media behaviour and to study an aspect of the non-journalistic practice of the media organization in the society in post-authoritarian Indonesia. It discusses the engagement of a major local media institution in the organization of the Surabaya Art Festival in the early 2000s. The involvement of one wealthy media institution, Jawa Pos, in the organization of Surabaya’s cultural art festival, therefore, could shape a new model of relationship between the media and the society in the Indonesian context. Based on interviews with several existing and ex-members of the festival committees and media documentations, this study argues that the political economy of the media interest has played a major role in determining the contents and management of the festival, disregarding the need to exhibit the remarkable cultural richness and innovations. In this particular cultural event, the media has played a significant role in supplying the funding for the festival, and consequently, the media control the power in conceptualising the city’s annual art festival since then. Yet, when the owner of the media institution chose to stop supporting the funding to the festival organization, the result was palpable. After the withdrawal of this major media magnate from the festival organization, the continuation of the Surabaya Art Festival has become troublesome and susceptible.